(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper makes an attempt to analyse the different cultural lifestyle of Indian people in the modern era. India is known for its richness in culture. It is ethnically and religiously diverse nation. Culture and lifestyle of people differ from place to place. In this novel, author focuses on the lifestyle of metropolitan Mumbai city and conventional Kolkata town. This paper aims to bring out the cultural difference within India.